Development of a TaqMan-based multiplex real-time PCR for simultaneous detection of porcine epidemic diarrhea virus, Brachyspira hyodysenteriae, and Lawsonia intracellularis - Ren, Jing; Li, Fujun; Yu, Xue; Li, Yang; Li, Meng; Sha, Yujie; Li, Xiaowen (Frontiers in Veterinary Science, 2024)
Introduction: PEDV, Brachyspira hyodysenteriae, and Lawsonia intracellularis, are highly contagious diarrheal pathogensdiseases that have caused significant harm to the global swine industry. Co-infections with multiple pathogens are common, making it challenging to identify the actual causative agents depending only on clinical information. It is crucial to develop a reliable method to simultaneously detect and differentiate these pathogens.Methods: Based on the conserved regions of the M gene of PEDV, NADH oxidase gene of B. hyodysenteriae, and the 16S rDNA gene of L. intracellularis, specific probes and primers for the multiplex real-time PCR assay were designed. The concentrations of primers and probes were optimized using a matrix method.The approach demonstrated high specificity and no cross-reactivity with major pathogens related to diarrheal diseases. It showed high sensitivity with a detection limit of 10 copies/μL for B. hyodysenteriae and L. intracellularis, and 100 copies/μL for PEDV, respectively. It also demonstrated high reproducibility and stability with low coefficients of variation. Results from the multiplex real-time PCR method were in complete agreement with the commercial singleplex real-time PCR kit for detecting PEDV, B. hyodysenteriae and L. intracellularis. Clinical data revealed single infection rates of 31.46% for PEDV, 58.43% for B. hyodysenteriae, and 98.6% for L. intracellularis. The co-infection rates were 16.85% for PEDV + B.